2021
DOI: 10.4103/2221-1691.303607
|View full text |Cite
|
Sign up to set email alerts
|

Borassus flabellifer L. crude male flower extracts alleviate cisplatin-induced oxidative stress in rat kidney cells

Abstract: Objective: To investigate the effects of Borassus flabellifer L. extracts on antioxidant activity, maintenance of cellular redox, and mitochondrial function in cisplatin-induced kidney injury. Methods: The extracts of Borassus flabellifer were obtained from crude male flowers using ethyl acetate and methanol. The antioxidant potential was evaluated by 2,2-azino-bis-(3-ethylbenzothiazoline- 6-sulfonic acid), 2,2-diphenyl-1-picrylhydrazyl, and ferric redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The total phenolic content in plant extracts of B. flabellifer male flower ethanolic extract depends on the polarity of solvent used for extraction [ 15 ]. Tusskorn et al reported that B. flabellifer flowers extracted with methanol and ethyl acetate had phenolic contents of 159.3 ± 0.3 and 90.0 ± 0.0 mg GAE/g extract, respectively [ 16 ]. The results suggested that the total phenolic content in B. flabellifer male flower’s ethanolic extract was significantly greater than the extracts from methanol and ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total phenolic content in plant extracts of B. flabellifer male flower ethanolic extract depends on the polarity of solvent used for extraction [ 15 ]. Tusskorn et al reported that B. flabellifer flowers extracted with methanol and ethyl acetate had phenolic contents of 159.3 ± 0.3 and 90.0 ± 0.0 mg GAE/g extract, respectively [ 16 ]. The results suggested that the total phenolic content in B. flabellifer male flower’s ethanolic extract was significantly greater than the extracts from methanol and ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH scavenging activities of B. flabellifer male flower extracted by different types of solvents have been reported. Tusskorn et al showed that the male flower of B. flabellifer extracted by ethyl acetate and chloroform had the IC 50 values of 287.03 ± 6.90 and >1000 µg/mL, respectively [ 16 ]. Kavatagimath et al reported that the B. flabellifer male flower extracted by 95% ethanol and butylated hydroxytoluene had the IC 50 values of 460 and 419 µg/mL, respectively [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin causes autophagy, DNA damage, cytoplasmic organelle failure, use particularly in the endoplasmic reticulum, and mitochondrial damage, all of which activate apoptotic pathways and cause cellular harm through oxidative stress and inflammation ( 2 3 ). In other investigations, cisplatin therapy increased oxidative stress in the kidneys of animal models ( 5 6 7 ). However, it is still unclear how the various mechanisms interact and eventually contribute to renal damage.…”
Section: Introductionmentioning
confidence: 84%
“…Oxidative stress induction in the large region of renal tissues causes all of these damages. Numerous investigations have documented the qualitative effects of cisplatin therapy on renal tissue in laboratory animals ( 5 6 7 ). Harmine treatment also reduced tubular necrosis and glomerular damage in the cisplatin-treated groups.…”
Section: Discussionmentioning
confidence: 99%